Mobility as a Service Concept within the Sustainable Development Policy Context - Nikolova, Christina (Research Papers, 2018)
The main topic for research in the field of deployment of Mobility as a service (MaaS) concept is related to the sustainable transport development opportunities. With regards to this, a large number of projects have been launched on the European level and their impact on transport sustainability has been evaluated. MaaS is an instrument for coordination and concentration of all scientific research on the deployment of information and communication technologies in transport, consolidating the efforts of wide variety of experts working on the implementation of innovative transport services.The article clarifies the essence and the role of MaaS concept for the development of different modes of transport as well as for enhancing transport services effectiveness. It studies the main aspects and elements of this concept in order to achieve transport sustainability. The article presents a review of MaaS concept’s development up to now and it outlines the perspectives for the future. The main benefits and risks related to the deployment of MaaS are generalized in the conclusion.